Intraparenchymal Renal Artery Pseudoaneurysm and Arteriovenous Fistula on a Solitary Kidney Occurring 38 Years after Blunt Trauma - Daniel Benamran; Benedicte de Clippele; Frank Hammer; Bertrand Tombal (Case Reports in Urology)
Pseudoaneurysm and arteriovenous fistulae of the renal artery are rare complications of kidney trauma. They commonly result from open traumas and occur within days after the injury. Common symptoms include acute haematuria, pain, or hypertension. We report the case of a fifty-three-year-old man presenting with symptomatic complex chronic high flow kidney arteriovenous fistula with interposition of a pseudoaneurysmal pouch and arterial aneurysmal dilatation in a solitary left kidney 38 years after a blunt trauma. Those conditions were successfully treated by endovascular embolization followed by regular radiologic, biological, and clinical follow-up. To the best of our knowledge, few similar cases were reported more than 20 years after trauma. However, no case combining an arteriovenous fistula and a pseudoaneurysm revealing as late as 38 years after trauma was found. In addition, management of those conditions on a solitary kidney and outcomes has not been described. We believe that our case depicts the clinical presentation and management of this rare entity that should not be unrecognized due to its potential lethal implications.